Adaptation of classical literature text to fit into a contemporary Singapore context : hawker - Chua, Gerald Jia Jun (Nanyang Technological University, 2020)
Hawker is a stylized 3D animated short film directed and animated by Chua Jia Jun Gerald over 3 semesters for his final year project at Nanyang Technological University (NTU), School of Art, Design and Media (ADM). Hawker is produced through the use of Autodesk Maya, a 3D Computer Animation software, for a visual and audio representation of the adaptation of classical literature text to fit into a contemporary Singapore context.